Study Survey of Worker’s Environment at Used Goods Shop in El. Mount Sarik, Padang City - Mahaza, Mahaza; Nur, Erdi; Adriyanti, Sri Lestari; Arlinda, Sari; Herwati, Herwati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
There are quite a lot of used goods storage places, such as Gunung Sarik Village, which gives an overview of the working environment conditions, workers in carrying out their work lack the awareness to wear personal protective equipment (masks), gloves and shoes while working. The population of this research is entrepreneurs and all workers who work in used goods shelters totaling 30 people. The instruments used are questionnaires and observation sheets. Data were obtained through interviews using a questionnaire. Data analysis uses the stages of environmental risk analysis which include the identification of hazards, and risk characteristics. Furthermore, the data is presented in the form of tables and narratives. The results of the study are environmental factors in the proper work of storing used goods that are at risk of work accidents, including work tools, physical and chemical work environment, nature of work, work methods, and work processes. More than half (53%) of workers in used goods storage facilities do not wear Personal Protective Equipment (PPE) when working. 26.7% of workers feel subjective complaints at work. The complaints they feel are Loss of Sense of Touch in the hands, Irritation of the eyes, and Blurred Eyes. For used goods storage managers, provide personal protective equipment such as (Safety glasses, masks, gloves, and gloves for workers to work) Conduct coaching activities for workers in wearing personal protective equipment to protect themselves against work hazards that will occur and for those who have experienced Subjective complaints such as eye irritation and blurry eyes should always wear safety glasses at work. Abstrak: Tempat penampungan barang bekas yang cukup banyak seperti Kelurahan Gunung Sarik diperoleh gambaran kondisi lingkungan kerja, pekerja dalam melakukan pekerjaannya kurang memiliki kesadaran untuk memakai alat pelindung diri (masker), sarung tangan dan sepatu selama bekerja. Populasi penelitian adalah pengusaha dan semua pekerja yang bekerja di tempat penampungan barang bekas berjumlah 30 orang Instrumen yang digunakan adalah Kuesioner dan lembar observasi. Data diperoleh melalui wawancara dengan menggunakan kuesioner. Analisis data menggunakan tahapan pada analisis risiko lingkungan yang meliputi identifikasi bahaya, dan karakteristik risiko. Selanjutnya data disajikan dalam bentuk tabel dan narasi. Hasil penelitian adalah Faktor-faktor lingkungan di tepat keja penyimpanan barang bekas yang berisiko kecelakaan kerja antara lain: alat kerja, lingkungan fisik dan kimia kerja, sifat pekerjaan, cara kerja, dan proses kerja. Lebih dari separoh (53%) Pekerja ditempat penyimpanan barang bekas tidak memakai Alat Pelindung Diri (APD) saat bekerja. 26,7% dari pekerja merasakan keluhan subjektif dalam bekerja keluhan yang dirasakan adalah Kehilangan Indra Peraba pada tangan, Iritasi pada mata, Mata Kabur. Untuk Penegelola Penampungan Barang bekas menyediaan Alat Pelindung diri seperti (Kaca mata Safety, Masker, Sarung Tangan, Sapetu untuk pekerja untuk bekerja Mengadakan kegiatan pembinaan kepada tenaga kerja dalam memakai aalat pelindung diri untuk melindungi diri terhadap bahaya kerja yang akan terjadi dan bagin yang sudah mengalami keluhan subyektif seperti Iritasi pada mata dan mata kabur seharusnya selalu memakai Kaca Mata safety dalam bekerja.